The Role of Manuka Honey in Protecting Against Cochlear Hair Cell Damage Caused by Diabetes Mellitus in Rats, Assessed Through Otoacoustic Emission - Simatupang, Sholahuddin Adlan; Adnan, Adlin; Harahap, M. Pahala H. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Diabetes mellitus is an escalating public health concern worldwide, with Indonesia being one of the countries heavily affected and facing a projected increase in cases. This condition is known to cause a range of complications, including hearing loss, which is frequently observed in diabetic individuals. This study aims to investigate the potential protective effect of honey against cochlear damage induced by diabetes mellitus. This ex-vivo experimental study applied a pretest-posttest control group design. Conducted over five months at the FMIPA USU Animal Laboratory, the study involved 25 healthy adult male Rattus norvegicus Wistar rats (150–250 grams, aged 2–3 months). The rats were divided into three treatment groups and assessed before and after honey administration on days 0, 3, 6, 9, and 12. SNR value differences were analyzed using Repeated Measures ANOVA or the Friedman test. Administration of honey at a dose of 1 g/kg body weight was more effective in preventing the decline of SNR values in diabetic rat models compared to the 2 g/kg dose. Honey demonstrates a protective effect against cochlear hair cell damage in diabetic Rattus norvegicus, as evidenced by SNR values from OAE assessments.